Impact localization on rigid surfaces using Hermitian angle distribution for human-computer interface applications - Nguyen, Quang Hanh (2020)
We propose an algorithm to localize impacts on rigid surfaces using induced vibration signals. This allows for the conversion of daily objects, such as tabletops and glass panels, into human-computer touch interfaces using low-cost piezoelectric sensors. Impact localization is achieved by estimating the time-of-arrivals and subsequently time-difference-of-arrivals of the sensor-received signals. Time-of-arrival estimation is highly challenging with increasing source-sensor distance due to the occurrence of a gradual noise-to-signal transition at the sensor output. We address this problem by first converting the signal into Hermitian angle distributions. The time-varying probability contributions of the background noise and vibration signal in each of the distributions are subsequently monitored to identify the instant when the signal begins to dominate the noise, signifying the signals arrival. The proposed framework also allows simultaneous time-of-arrival estimation across all the sensors to minimize errors in the resultant time-difference-of-arrival estimates. Experimental results show that the proposed algorithm outperforms existing techniques for source localization on solid surfaces of different materials.